Water Financing Programs in the Philippines: Are We Making Progress? - Gilberto M. Llanto (Philippine Institute for Development Studies (PIDS), 2013)
The paper argues the case for developing more innovative financing schemes for the water supply sector. The use of traditional ODA-dependent financing channeled through government lending institutions has a somewhat moderate success record in developing and improving the water supply sector. There are limitations to the use of public funds and public institutions in financing water delivery systems and it will be helpful to think of PPP or PSP arrangements or schemes that can come up with innovative solutions to address the issues in this sector. The Philippine Water Revolving Fund (PWRF) is one such innovative financing model and there could be others but developing and establishing such models will require the collaborative effort of the concerned stakeholders. Government lending institutions must be forced by policymakers to collaborate with the private sector in solving the long-standing water supply problem for a very large segment of the population. Those government lending institutions have the advantage of ODA funds, which they traditionally use to lend to target borrowers. The ODA funds can be blended with private sector resources, including credit guarantees that have been demonstrated as good credit enhancements, to lower the cost of financing water supply projects.
Keywords: 330; Philippines; Local Government Units (LGUs); waterless municipalities; water supply systems; LWUA; MDFO; government financial institutions; output-based aid; MDG